2022
DOI: 10.5455/medscience.2022.07.156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of needle bevel position in arteriovenous fistula cannulation and bleeding during hemodialysis

Abstract: This study investigated the effect of needle bevel position during arteriovenous fistula cannulation on bleeding stop time in patients with chronic hemodialysis. An arteriovenous fistula puncture was performed on patients using the needle bevel up and down and the bleeding stop time was recorded in minutes. The outcomes of the two techniques were compared. The anticoagulant type used did not affect the bleeding stop time in the 55 patients with hemodialysis included in this study. On separately considering pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Uston et al studied bevel position in conjunction with anticoagulant to examine the coagulation time in hemodialysis patients. It was found that the coagulation time of needle bevel down was shorter than that of needle bevel up [9]. David et al investigated venous needle flow to examine the fluid dynamic effects of cannulation by considering needle angle, blood flow rate, needle depth, and back eye.…”
Section: Introductionmentioning
confidence: 99%
“…Uston et al studied bevel position in conjunction with anticoagulant to examine the coagulation time in hemodialysis patients. It was found that the coagulation time of needle bevel down was shorter than that of needle bevel up [9]. David et al investigated venous needle flow to examine the fluid dynamic effects of cannulation by considering needle angle, blood flow rate, needle depth, and back eye.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis patients with an arteriovenous fistula (AVF) or arteriovenous graft (AVG) are at increased risk of bleeding due to the coagulopathy of end-stage kidney disease [ 1 ] and the use of systemic anticoagulation in the hemodialysis circuit [ 2 ]. The risk of prolonged bleeding specifically after needle removal from AVF or AVG cannulation sites is also impacted by needle position [ 2 , 3 ] cannulation technique (buttonhole versus rope-ladder) [ 4 ], vascular access integrity, namely whether there is associated pseudoaneurysm/aneurysm, stenosis or infection [ 5 ]. Prolonged post-cannulation bleeding is associated with poor outcomes including increased rates of anemia [ 6 ], quality of life disruptions [ 7 ], and fatal catastrophic hemorrhage [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%